Distribution Of Lip Print Patterns Among Primary School Children In West Bengal Using The Suzuki–Tsuchihashi Classification: A Cross-Sectional Forensic Study (Journal of Forensic Medicine & Toxicology, 2026)
Cheiloscopy, the study of lip-print patterns, has emerged as a promising supplementary tool for personal identification due to the uniqueness, permanence, and stability of lip grooves. Despite its potential, population-specific data—espe cially among children—remain limited, and standardized protocols for collection and analysis are lacking. This cross-sec tional descriptive study was conducted across ten districts of West Bengal, India, involving 616 primary school students aged 6–10 years. Lip prints were collected prospectively using a standardized methodology. Each print was divided into six quadrants and classified using the Suzuki and Tsuchihashi system (Types I, I’, II, III, IV, V). Results revealed that Type II (Branched) was the predominant pattern across all districts and all six quadrants, demonstrating strong uni formity within the population. Type III (Intersected) was the second most common in upper quadrants, whereas Type I (Complete Vertical) dominated as the secondary pattern in lower quadrants. Notably, Type V (Undetermined) was absent in every quadrant and district. District-wise variations existed but did not alter the overall dominance of Type II. The study highlights significant consistency with previous Indian and international research, reinforcing the prevalence of the branched pattern in diverse populations. By focusing on a young demographic, the study adds valuable baseline data for early-life lip print characteristics.
Keywords: Cheiloscopy; Lip prints; Forensic identification; Suzuki-Tsuchihashi classification; West Bengal population; Personal identification.